Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Produktivitas Kerja Karyawan pada PT Vidira Eshan Abadi: The Effect of Work Discipline and Work Motivation on Employee Work Productivity at PT Vidira Eshan Abadi - Nazwa Pramesti Sutopo; Desy Suryani; Martinus Pramesti Wahyu Purnomo (Jurnal Manajemen dan Akuntansi Cakrawarti, 2026)
Work productivity is a key indicator of organizational success, influenced by work discipline and work motivation. This study aims to analyze the effect of work discipline and work motivation on employee productivity at PT Vidira Eshan Abadi. The research method used a quantitative approach with primary data obtained through questionnaires distributed to 50 respondents. The analysis was conducted using partial tests (t-test), simultaneous tests (F-test), coefficient of determination (R²), and regression coefficients with the assistance of SPSS version 27. The results show that work discipline has a significant effect on productivity, with a t-count value of 2.670 > t-table 2.011 and a significance value of 0.010 < 0.05. Work motivation also has a significant effect, with a t-count value of 4.369 > t-table 2.011 and a significance value of 0.000 < 0.05. Simultaneously, work discipline and work motivation have a significant effect on productivity, as indicated by an F-count value of 23.311 > F-table 3.20 with a significance value of 0.000 < 0.05. The coefficient of determination (R²) value is 49.8%, while the remaining 50.2% is influenced by other factors outside this study. The regression equation obtained is Y = 7.015 + 0.251X1 + 0.416X2 + e. The interpretation of this equation indicates that an increase in work discipline and work motivation will drive an increase in work productivity.